A mediating and multigroup analysis of customer loyalty. Issue 6 (December 2016) - Picón-Berjoyo, Araceli; Ruiz-Moreno, Carolina; Castro, Ignacio
Abstract: Loyalty is configured here as a key determinant of firm performance. Many studies have proposed models that analyze the relationship between loyalty and its main determinants: perceived value (PV), satisfaction, and perceived switching costs (PSC). Thus, the first aim of this work is to validate a model of the direct and indirect relationships between these variables and loyalty, analyzing the mediating roles of both PSC and satisfaction in the relationship between PV and loyalty. The second aim is to analyze the influence of customer psychographic characteristics – tendency toward loyalty (based on customer involvement and propensity toward switching) – on the proposed model in the insurance industry. The results show that (a) PV has a direct influence on affective loyalty and an indirect influence through two mediating variables, while only PSC plays a mediating role in the case of behavioral loyalty; (b) there were significant differences between customers with a high tendency toward loyalty and those with a low tendency toward loyalty, in the relationship between satisfaction and affective loyalty and in the relationship between PSC and both affective and behavioral loyalty; and (c) the proposed model presents greater explanatory power for customers with a higher tendency toward loyalty.